An integrated approach to tracking mandibular position relative to incisal and condylar envelopes of motion during intraoral clinical procedures: a new look at TMJ movements - Li, Jing-Sheng; Ramsay, Douglas S.; Burke, Andrea B.; Huang, Greg J.; Arce-McShane, Fritzie I. (Frontiers in Dental Medicine, 2025)
Current methods for tracking temporomandibular joint (TMJ) movements are difficult to perform during dental procedures. Yet precise and accurate quantification of mandibular movements is critical for understanding temporomandibular biomechanics and how certain movements may contribute to temporomandibular dysfunction. This is particularly relevant to clinical procedures that might move the mandible near or beyond its functional range of motion. We present a novel approach that integrates cone-beam computed tomography, optical intra-oral scans, and six degree-of-freedom electromagnetic sensor data to quantify mandibular movements. This method employs rigid body transformations to generate subject-specific three-dimensional (3D) envelopes of motion and assess whether incisal and condylar landmarks remain within their functional 3D envelopes of motion. We demonstrate the clinical utility of this approach through simulated mandibular poses presented relative to the limits of incisal and condylar envelopes created from that individual's voluntary border movements. Our findings reveal that condylar or incisal points in simulated mandibular poses are located beyond their normal motion envelopes, highlighting the importance of simultaneous monitoring of incisal and condylar landmarks. This methodology provides a clinically relevant tool for understanding temporomandibular biomechanics and it has the potential to signal clinicians when jaw movements during dental and oral surgical procedures approach or exceed the jaw's functional range of motion and such corrective feedback could prevent adverse effects on the TMJ.